Human rights for children and youth sociocultural differentiation, resistance and unity - Reis, Magali; Isidório, Marcelo S. (Sociological studies of children and youth, 2019)
This volume, written by experts in the field across 3 different continents, explores the condition of childhood with a particular focus on the fundamental rights of children and young people and how this translates into living conditions in different socio-cultural realities